PERSEPSI PEMUSTAKA TERHADAP SIKAP PUSTAKAWAN DALAM MEMBERIKAN LAYANAN DI MAN 2 KOTA BANJARMASIN - Ismayanti Yanti; Anis Masruri (Unversitas Muhammadiyah Mataram, 2023)
This article aims to find out the attitude of librarians in serving users at the MAN 2 library in Banjarmasin City, namely being attentive, helpful, considerate, polite and caring. The research method used is qualitative with the type of research used is descriptive. The data analysis used is the data collection technique through written interviews using the Google Forms application. The results showed that the user's perception of the attitude of librarians in serving at the MAN 2 library in Banjarmasin City was good and friendly in their service. However, from the assessment of initiatives to help without being asked, each is lacking or there is still a lack of attention to the needs of users. The overall attitude of the librarians was classified as good from the results of the written interviews taking into account several assessments, namely being attentive, helpful, considerate, polite and caring. The overall assessment is taken into consideration by the librarians to assess the librarian's attitude, from this assessment the librarian has almost fulfilled the attitude that is responsible for them. Librarians need to increase initiative and awareness to provide technical guidance in information retrieval that users need to know how to quickly use information retrieval tools.Keyword: User Perception, Librarian Attitude